2015
DOI: 10.1111/hiv.12253
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to antiretroviral treatment initiation in rural KwaZulu‐Natal, South Africa

Abstract: In this rural South African setting, barriers to ART initiation differed for men and women. Supportive individual- and household-level interventions should be developed to guarantee rapid ART initiation taking account gender specificities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 56 publications
2
19
0
Order By: Relevance
“…As well, subjects who knew PLHIV who disclosed their HIV status to relatives or friends got better social support to ease stigma and discrimination. 25,26 Surprisingly, subjects out of the catchment area were 59% less likely to have delayed ART initiation (AOR=0.41, 95% CI=0.18-0.91). In contrast, studies in Sub-Saharan Africa reported the distance from HIV care site to be associated with low engagement on HIV care.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…As well, subjects who knew PLHIV who disclosed their HIV status to relatives or friends got better social support to ease stigma and discrimination. 25,26 Surprisingly, subjects out of the catchment area were 59% less likely to have delayed ART initiation (AOR=0.41, 95% CI=0.18-0.91). In contrast, studies in Sub-Saharan Africa reported the distance from HIV care site to be associated with low engagement on HIV care.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, studies in Sub-Saharan Africa reported the distance from HIV care site to be associated with low engagement on HIV care. 26 – 28 This clinical scenario could be explained by subjects who were distant from the HIV care site might have understood benefit of ART care, but might have low confidence to initiate ART in their locality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laboratory-based investigations and clinical evaluation should be conducted to assess drug tolerance and adverse drug effects [ 11 ]. Factors related to patients, health professionals, and health institutions all have an impact on adherence to ART [ 12 , 13 ]. Patient-related factors that influence ART adherence include sex, age, residence, educational status, occupation, marital status, income, disclosure status, substance abuse history, clinical, and medication-related factors [ 12 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, the World Health Organization (WHO) recommended that antiretroviral therapy (ART) be initiated by everyone living with HIV as soon as possible due to the impact of sustained ART on reduced mortality, morbidity, and sexual transmission to HIV-negative partners (Cohen et al, 2016;INSIGHT START Study Group et al, 2015;WHO, 2015 Eswatini, 2018), individuals sometimes delay or choose to not initiate ART (Ahmed et al, 2018;Larsen et al, 2019;Lee et al, 2019;Maughan-Brown et al, 2018;Pell et al, 2018;Plazy et al, 2015). Recent population-level surveys have found that 30% of South Africans and ∼12% of people living with HIV in Eswatini, Kenya, and Zambia who know their HIV diagnosis are not using ART (Human Sciences Research Council, 2018;Ministry of Health, Zambia, 2017;NASCOP, 2020;Swaziland Ministry of Health, 2017).…”
Section: Introductionmentioning
confidence: 99%